A Study on Impact of Climate Change on Wheat Production in Kurukshetra District of Haryana - Chetna; Pushpa; Aditi; Urmil Verma (Journal of the Indian Society of Agricultural Statistics, 2025)
The present paper attempts to study the effect of Wheat production in the Kurukshetra area of Haryana, India, is affected by changes in meteorological conditions. The study examined 35 years of time series data on wheat yield as well as weekly data on five weather variables for the crop season from 1985-86 to 2019-20. Using weather indices and time trend as regressor variables and wheat yield as regress and the effect of various factors was investigated using step-wise regression analysis. It has been found that weighted weather indices of each weather variable including time trend have exhibited significant effect on the wheat yield. It has also been found that rise in all five weather variables except relative humidity has been detrimental to wheat yield during harvesting phase of the crop. The overall results indicate the fact that changes in climatic variables show detrimental as well as beneficial the role depending upon the phases of crop production in getting out its final output. On the basis of root mean square error the Model-P5 has been proven to be best among all the models the average percent standard error (PSE) value of the Model-P5 is 0.94 which shows that these models are better for forecast. Principal component techniques are best created model.